What About Inclusive Education and ICT in Italy: a Scoping Study - Volpe, Valentina Della (European Scientific Journal, ESJ, 2016)
Strategies and approaches to inclusion in the classroom are important in developing a high quality, inclusive experience for students with Special Education Needs. Generally, strategies are not geared towards specific exceptionalities, but are instead designed to be implemented across exceptionality categories. Pavone (2014) and de Anna, Gaspari, Mura (2015) determined through their systematic literature review and research results that co-operation among staff, commitment and accountability to the teaching of all students, differentiation of instruction, and recognizing “that social interaction is the means through which student knowledge is developed” are key to successful inclusion of students with SEN. This paper looks at the issue of school inclusion by referring to the most recent laws about the inclusive education of students with special educational needs in Italy. Inclusive education means that all students attend and are welcomed by their neighbourhood schools in age-appropriate, regular classes and are supported to learn, contribute and participate in all aspects of the life of the school. Inclusive education is about how we develop and design our schools, classrooms, programs and activities so that all students learn and participate together. So ICT should be considered as a key tool for promoting equity in educational opportunities, that is using ICT to support the learning of learners with disabilities and special educational needs in inclusive settings within compulsory education. The paper also argues how the Italian teachers can realized good practices for inclusion through the use of ICT.